Bio-Hydrogen Production from Pineapple Waste Extract by Anaerobic Mixed Cultures - Chakkrit Sreela-or; Alissara Reungsang (Energies, 2013)
A statistical experimental design was employed to optimize factors that affect the production of hydrogen from the glucose contained in pineapple waste extract by anaerobic mixed cultures. Results from Plackett-Burman design indicated that substrate concentration, initial pH and FeSO4 concentration had a statistically significant (p ≤ 0.05) influence on the hydrogen production potential (Ps) and the specific hydrogen production rate (SHPR). The path of steepest ascent was undertaken to approach the optimal region of these three significant factors which was then optimized using response surface methodology (RSM) with central composite design (CCD). The presence of a substrate concentration of 25.76 g-total sugar/L, initial pH of 5.56, and FeSO4 concentration of 0.81 g/L gave a maximum predicted Ps of 5489 mL H2/L, hydrogen yield of 1.83 mol H2/mol glucose, and SHPR of 77.31 mL H2/g-volatile suspended solid (VSS) h. A verification experiment indicated highly reproducible results with the observed Ps and SHPR being only 1.13% and 1.14% different from the predicted values.